2019
DOI: 10.18821/0016-9900-2017-96-2-137-143
|View full text |Cite
|
Sign up to set email alerts
|

Complex technology for water and wastewater disinfection and its industrial realization in prototype unit

Abstract: Usage of complex automated electrolysis unit for drinking water disinfection and wastewater oxidation and coagulation is scoped, its ecological and energy efficiency is shown. Properties of technological process of anolyte production using membrane electrolysis of brine for water disinfection in municipal pipelines and potassium ferrate production using electrochemical dissolution of iron anode in NaOH solution for usage in purification plants are listed. Construction of modules of industrial prototype for ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Domestic and foreign research confirmed their effectiveness in various fields and resulted in a number of patents [10][11][12][13][14][15][16][17][18]. Some studies featured advanced production methods for electrolyzers and activated water with improved properties [19][20][21][22]. An efficient electrocatalyst possesses a number of certain properties.…”
Section: Introductionmentioning
confidence: 99%
“…Domestic and foreign research confirmed their effectiveness in various fields and resulted in a number of patents [10][11][12][13][14][15][16][17][18]. Some studies featured advanced production methods for electrolyzers and activated water with improved properties [19][20][21][22]. An efficient electrocatalyst possesses a number of certain properties.…”
Section: Introductionmentioning
confidence: 99%
“…Food production enterprises, including meat-processing ones are the sources of antropogenic and technogenic impact of its wastewaters on the natural water bodies. Development of technologies for purification and utilization of industrial wastes requires usage of express-tests, which allow one to obtain fast and qualitative characterization of wastes and wastewaters [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%